Response of boro rice (Oryza sativa L.) genotypes to genetic diversity and character association for yield associated traits: Genetic diversity and yield traits in boro rice - Islam, T; Huda, K M K; Rashid, M Harun Ur; Johora, FT; Parveen, S; Islam, MZ; Rahmatullah, R; Islam, R (Bangladesh Journal of Agriculture, 2026)
An experiment was conducted at the research field of Sher-e-Bangla Agricultural University, Dhaka-1207 during the Boro season (December 2020 to May 2021) using twenty-three Boro rice genotypes to evaluate genetic variability, heritability, genetic advance, correlation, path analysis and genetic diversity for yield-related traits. The experiment followed a randomized complete block design (RCBD) with three replications. Significant variation among genotypes were observed for all fourteen studied traits. The highest phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) were observed (48.90% and 47.72%, respectively) for the number of unfilled grains per panicle. High heritability along with high genetic advance in percentage of mean was recorded for leaf sheath length, number of unfilled grains per tiller, number of primary branches per panicle, panicle length and thousand grains weight, suggesting these traits are governed by additive gene action. Yield per hill was positively and significantly correlated with the number of filled grains per tiller, unfilled grains per tiller and thousand grains weight. Traits such as leaf blade length, stem length, effective tillers, panicle length and branching showed positive direct effects on yield. The genotypes were grouped into four clusters. Based on cluster means and genetic parameters, G20 (BRRI dhan96), G1 (BR 1), G3 (BR 5) and G5 (BR 14) were identified as promising lines. Crosses among clusters I, II, III and IV especially involving cluster IV are recommended for future hybridization to exploit heterosis in breeding programs. Bangladesh J. Agri. 2025, 50(2): 120-131